Comment on Professor Schwenzer's paper - Whittington, Nicholas (Victoria University of Wellington Law Review, 2005)
The author comments on Ingeborg Schwenzer's paper found in this volume (Ingeborg Schwenzer "The Danger of Domestic Preconceived Views with Respect to the Uniform Interpretation of the CISG: The Question of Avoidance in the Case of Non-Conforming Goods and Documents" (2005) 36 VUWLR 795). This author argues for a "single standard concept" in relation to the application of the Convention on Contracts for the International Sale of Goods ('CISG'), meaning that the broad and ambitious document should have a uniform application. Unfortunately, the author notes that the CISG's application has been anything but in both the international and domestic contexts. The author provides potential solutions to this lack of uniformity: first, encourage decision-makers to have regard to case law from other countries; and secondly, encourage courts, when dealing with the CISG, to distance themselves from domestic preconceptions and to look at the case through CISG-tinted glasses.